Dance and choreographic design in the body and space: an interdisciplinary exploration (2025)
This study examines the rich interdisciplinary interface between dance and design, focusing particularly on the interplay between body, space, and time in choreographic practices. It posits that dance is not merely a performance art but a dynamic system of embodied knowledge and spatial intelligence that intersects with the conceptual and practical frameworks of design. Drawing from both theoretical and practical perspectives, this paper emphasizes how dancers and choreographers use the human body not just as a medium of expression but as a site of emotional, cultural, and spatial negotiation. This paper begins by exploring four core elements common to both disciplines—body, space, time, and —and how they serve as foundations for both dance expression and design formulation. It investigates the body not only as a physical entity but also as a symbolic and narrative agent capable of transmitting emotions, cultural values and social ideologies. Citing influential scholars such as José Gil, Margolis, and Hanna, this study describes how the dancing body forms and reforms space, becoming both the subject and object of aesthetic experience. Spatiality in dance is then examined not only as a background but also as an active participant in meaning-making. From stage layout and scenography to costume design and digital projections, this paper analyzes how space is choreographed and designed to influence movement, evoke emotions, and heighten audience engagement. The performative space, in this context, becomes a canvas for embodied storytelling, where design scaffolds the motion and emotion of dance. Additionally, this study reflects on how costume design contributes to the readability of performance, affecting both audience perception and the dancer’s expression. Costumes are framed not as decorative elements but as integral to the storytelling function of dance, identity communication, cultural context and character differentiation.